Gene expression and promoter methylation of angiogenic and lymphangiogenic factors as prognostic markers in melanoma - Monteiro, Ana Carolina; Muenzner, Julienne K.; Andrade, Fernando; Rius, Flávia Eichemberger; Ostalecki, Christian; Geppert, Carol-Immanuel; Agaimy, Abbas; Hartmann, Arndt; Fujita, André; Schneider-Stock, Regine; Jasiulionis, Miriam Galvonas (Molecular Oncology, 2019)
The high mortality rate of melanoma is broadly associated with its metastatic potential. Tumor cell dissemination is strictly dependent on vascularization; therefore, angiogenesis and lymphangiogenesis play an essential role in metastasis. Hence, a better understanding of the players of tumor vascularization and establishing them as new molecular biomarkers might help to overcome the poor prognosis of melanoma patients. Here, we further characterized a linear murine model of melanoma progression and showed that the aggressiveness of melanoma cells is closely associated with high expression of angiogenic factors, such as Vegfc, Angpt2, and Six1, and that blockade of the vascular endothelial growth factor pathway by the inhibitor axitinib abrogates their tumorigenic potential in vitro and in the in vivo chicken chorioallantoic membrane assay. Furthermore, analysis of The Cancer Genome Atlas data revealed that the expression of the angiogenic factor ANGPT2 (P-value = 0.044) and the lymphangiogenic receptor VEGFR-3 (P-value = 0.002) were independent prognostic factors of overall survival in melanoma patients. Enhanced reduced representation bisulfite sequencing-based methylome profiling revealed for the first time a link between abnormal VEGFC, ANGPT2, and SIX1 gene expression and promoter hypomethylation in melanoma cells. In patients, VEGFC (P-value = 0.031), ANGPT2 (P-value < 0.001), and SIX1 (P-value = 0.009) promoter hypomethylation were independent prognostic factors of shorter overall survival. Hence, our data suggest that these angio- and lymphangiogenesis factors are potential biomarkers of melanoma prognosis. Moreover, these findings strongly support the applicability of our melanoma progression model to unravel new biomarkers for this aggressive human disease.
CRIS-Team Scopus Importer:2019-06-18
Keywords: angiogenesis; biomarkers; DNA methylation; melanoma; prognosis